Radiation‐induced sensitivity of tissue‐resident mesenchymal stem cells in the head and neck region. Issue 9 (24th April 2019) - Spiegel, Jennifer L.; Hambrecht, Mario; Kohlbauer, Vera; Haubner, Frank; Ihler, Friedrich; Canis, Martin; Schilling, Arndt F.; Böker, Kai O.; Dressel, Ralf; Streckfuss‐Bömeke, Katrin; Jakob, Mark
Abstract: Background: Tissue‐resident mesenchymal stem cells (MSCs) possess the ability to migrate to areas of inflammation and promote the regeneration of damaged tissue. However, it remains unclear how radiation influences this capacity of MSC in the head and neck region. Methods: Two types of MSCs of the head and neck region (mucosa [mMSC] and parotid gland [pMSC]) were isolated, cultured and exposed to single radiation dosages of 2 Gy/day up to 10 days. Effects on morphology, colony forming ability, apoptosis, chemokine receptor expression, cytokine secretion, and cell migration were analyzed. Results: Although MSC preserved MSC‐specific regenerative abilities and immunomodulatory properties following irradiation in our in vitro model, we found a deleterious impact on colony forming ability, especially in pMSC. Conclusions: MSC exhibited robustness and activation upon radiation for the support of tissue regeneration, but lost their potential to replicate, thus possibly leading to depletion of the local MSC‐pool after irradiation